EFFECT OF 4P'S MARKETING MIX ON PURCHASE DECISION: (Case Study at UD. Rencana Baru Store) - Putri Hanifah; Sri Nuringwahyu; Dadang Krisdianto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the influence of the 4P's marketing mix on purchasing decisions. This type of research is quantitative. Data collection techniques using questionnaires. The number of samples is 100 respondents using SPSS Statistics V.20. Based on the Partial Test, the product has a significant effect on purchasing decisions at the UD. Rencana Baru store. This is indicated by t statistic > t table (1,432 > 1,965) and significant t is less than 0,05 (0,155 < 0,05). Meanwhile, price partially does not have a significant effect on purchasing decisions at the UD. Rencana Baru store, it can be proven by that t statistic < t table (0,493 < 1,965) and significant t is less than 0.05 (0,623> 0,05). Place has a significant effect on purchasing decisions at the UD. Rencana Baru store. This is indicated by t statistic > t table (5,452 > 1,965) and significant t is less than 0,05 (0,000 < 0,05). Promotion partially has no significant effect on purchasing decisions at the UD. Rencana Baru store. This can be shown by t statistic < t table (0,988 < 1,965) and significant t less than 0.05 (0,321> 0,05). According to Simultaneous Test, it can be seen that Product (X1), Price (X2), Place (X3), Promotion (X4) have a significant effect simultaneously on Purchase Decision (Y) at UD. Rencana Baru. Besides, multiple linear regression analysis test reveal that the Place (X3) is the variable that has the largest beta coefficient of 0,534, which becomes the dominant variable.